Reply to Discussion on: An investigation of the basement complex aquifer system in Lofa county, Liberia, for the purpose of siting boreholes - Elster, D; Holman, Ian P.; Parker, Alison (Geological Society, 2014)
Hydrogeological knowledge is vital for developing sustainable groundwater supplies globally. This is particularly true for the underpinning data from basement complex areas, such as those in Liberia, with complex hydrogeology and where past political instability has led to information and knowledge loss. The authors are therefore appreciative of the attention paid to their paper (Elster et al 2014) by Beeson and Jones (2014) and welcome the opportunity it provides for discussion on this important topic.